Philosophical Analysis of Restorative Justice: (Amnesty-Abolition) of President Prabowo Against Tom Lembong and Hasto Kristiyanto - Agam, Agam Ibnu Asa; Marcus, Marcus Priyo Gunarto; Mukhtasar, M. Mukhtasar Syamsuddin (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2025)
This study presents a philosophical analysis of the intersection between restorative justice and criminal law in the context of granting amnesty and abolition by President Prabowo Subianto to Tom Lembong and Hasto Kristiyanto. The primary focus of this study is to evaluate whether these policies are justifiable under a restorative framework, taking into account the principles of accountability, recognition, and reconciliation. Using normative legal research methods and philosophical approaches, this article argues that although amnesty and abolition are legitimate instruments for achieving political stability, their implementation risks eroding accountability if it is not transparent. Its main findings suggest that these actions are not completely restorative because they are top-down and stop the accountability process. However, it can align with restorative principles if a transparent, accountable, and recovery-oriented process accompanies it. This study concludes that the success of the restorative approach lies in the process, which demands public recognition, the participation of affected parties, and a sincere commitment to improvement.